Dual Role of the Histone Variant H2A.Z in Transcriptional Regulation of Stress-Response Genes. Issue 4 (3rd March 2017) - Sura, Weronika; Kabza, Michał; Karlowski, Wojciech M.; Bieluszewski, Tomasz; Kus-Slowinska, Marta; Pawełoszek, Łukasz; Sadowski, Jan; Ziolkowski, Piotr A.
Abstract : H2A.Z is removed from nucleosomes localized in genes upon transcriptional activation in response to drought stress conditions in Arabidopsis thaliana . Abstract: The influence of the histone variant H2A.Z on transcription remains a long-standing conundrum. Here, by analyzing the actin-related protein6 mutant, which is impaired in H2A.Z deposition, and by H2A.Z profiling in stress conditions, we investigated the impact of this histone variant on gene expression in Arabidopsis thaliana . We demonstrate that the arp6 mutant exhibits anomalies in response to osmotic stress. Indeed, stress-responsive genes are overrepresented among those hyperactive in arp6. In wild-type plants, these genes exhibit high levels of H2A.Z in the gene body. Furthermore, we observed that in drought-responsive genes, levels of H2A.Z in the gene body correlate with transcript levels. H2A.Z occupancy, but not distribution, changes in parallel with transcriptional changes. In particular, we observed H2A.Z loss upon transcriptional activation and H2A.Z gain upon repression. These data suggest that H2A.Z has a repressive role in transcription and counteracts unwanted expression in noninductive conditions. However, reduced activity of some genes in arp6 is associated with distinct behavior of H2A.Z at their +1 nucleosome, which exemplifies the requirement of this histone for transcription. Our data support a model where H2A.Z in gene bodies has a strong repressive effect on transcription, whereas in +1 nucleosomes, it is important for maintaining the activity of some genes.